Ruralization of students’ horizons: insights into Australian health professional students’ rural and remote placements - Smith, Tony (J Multidiscip Healthc, 2018)
INTRODUCTION: Health workforce shortages have driven the Australian and other Western governments to invest in engaging more health professional students in rural and remote placements. The aim of this qualitative study was to provide an understanding of the lived experiences of students undertaking placements in various nonmetropolitan locations across Australia. In addition to providing their suggestions to improve rural placements, the study provides insight into factors contributing to positive and negative experiences that influence students’ future rural practice intentions. METHODS: Responses to open-ended survey questions from 3,204 students from multiple health professions and universities were analyzed using two independent methods applied concurrently: manual thematic analysis and computerized content analysis using Leximancer software. RESULTS: The core concept identified from the thematic analysis was “ruralization of students’ horizons,” a construct representing the importance of preparing health professional students for practice in nonmetropolitan locations. Ruralization embodies three interrelated themes, “preparation and support,” “rural or remote health experience,” and “rural lifestyle and socialization,” each of which includes multiple subthemes. From the content analysis, factors that promoted students’ rural practice intentions were having a “positive” practice experience, interactions with “supportive staff,” and interactions with the “community” in general. It was apparent that “difficulties,” eg, with “accommodation,” “Internet” access, “transport,” and “financial” support, negatively impacted students’ placement experience and rural practice intentions. CONCLUSIONS: The study findings have policy and practice implications for continuing to support students undertaking regional, rural, and remote placements and preparing them for future practice in nonmetropolitan locations. This study may, therefore, further inform ongoing strategies for improving rural placement experiences and enhancing rural health workforce recruitment, retention, and capacity building.